2017
DOI: 10.4236/ce.2017.813145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of University Teachers’ Workplace Spirituality on Employee Engagement: Professional Commitment as Mediator

Abstract: The current research on workplace spirituality effect is mainly carried out in the west, lacking evidence of China background and attention to university teachers, although the groups are called soul engineer in China. In order to test the effect of workplace spirituality on employee engagement of Chinese university teachers, this study collected 239 samples by convenient sampling. The results of structural equation model test showed that the workplace spirituality of university teachers had a positive impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 20 publications
3
15
0
5
Order By: Relevance
“…This implies that 'the extent to which people feel engaged and immersed at work is therefore somewhat dependent on the extent to which they experience spirit in their work' (Breytenbach, 2016). A spiritual environment at workplace instils a love for work among employees as a result of which they become engaged in their work (Ke et al, 2017). Based on the above evidence, the authors propose that workplace spirituality can significantly predict work engagement.…”
Section: Workplace Spiritualitymentioning
confidence: 97%
See 1 more Smart Citation
“…This implies that 'the extent to which people feel engaged and immersed at work is therefore somewhat dependent on the extent to which they experience spirit in their work' (Breytenbach, 2016). A spiritual environment at workplace instils a love for work among employees as a result of which they become engaged in their work (Ke et al, 2017). Based on the above evidence, the authors propose that workplace spirituality can significantly predict work engagement.…”
Section: Workplace Spiritualitymentioning
confidence: 97%
“…Research exploring the relation between workplace spirituality and work engagement remains limited. Few empirical studies which have examined the relation between the two have shown that workplace spirituality is positively related to work engagement (Breytenbach, 2016;Ke, Zhang, Yan, & Fu, 2017;Singh & Gambhir, 2016;van der Walt, 2018). This implies that 'the extent to which people feel engaged and immersed at work is therefore somewhat dependent on the extent to which they experience spirit in their work' (Breytenbach, 2016).…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…Ashmos dan Duchon (2000) menggambarkan spiritualitas dalam kehidupan pribadi adalah pengalaman manusia dalam pencarian makna dan tujuan merupakan hal yang utama dan hidup dalam harmoni dengan orang lain dipandang sebagai sesuatu yang sangat penting meskipun harus bertentangan dengan arus nilai-nilai lain yang cenderung memacu perolehan materi. Spiritualitas pada guru ditemukan berhubungan dengan keterlibatannya dalam bekerja dan kemudian berdampak pada perilaku dan kinerjanya di organisasi (Ke, Zhang, Yan & Fu, 2017). Boone, Fite, Reardon (2010), seorang guru yang memiliki spiritualitas akan berupaya untuk meningkatkan pengetahuannya sebagai guru, pengetahuan interpersonal yang berkaitan dengan hubungannya dengan siswa dan komunitas pendidikannya, dan pengetahuan intra personal yaitu pengetahuan guru tentang diri dan komitmen atas kepedulian dan etos kerjanya untuk terus belajar.…”
Section: Pendahuluanunclassified
“…Psychologically unconstructive variables; stress, anxiety, weakness, headache, and pains put negative effects on one's Workplace spirituality is a multi-dimensional (Paul et al, 2020) and broader construct (Garg, 2020) that develop humans enthusiasm and truthfulness (Zhang, 2020), a hub of presenting religious activities (Baker & Lee, 2020), the search for meaningful and purpose focusing inner satisfaction of thoughts and behaviours (Simon, 2020) and robustly involved in religious interruptions (Joshi et al, 2021). Workplace spirituality refers to teachers religious beliefs on their excellent manners (Khorshid, 2015), engineers of teacher's souls (Ke et al, 2017), and teacher's innate self-awareness for inner satisfaction (Utami et al, 2021). Workplace spirituality reflects teachers inner enthusiasm towards the institution's betterment (Amri et al, 2021;Rezapouraghdam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is significantly better than others power of convincing (Estrada et al, 2021;Salazar & Khanwewal, 2021). Mindfulness is teachers insight and judgments that are interlinked with their students achievements and focuses on their cognitive abilities, thoughts and actions (Ke et al, 2017). Mindfulness has great concern towards teachers present, past and future concerns.…”
Section: Introductionmentioning
confidence: 99%